Effect of (m)RVD-hemopressin against Aβ1-42-induced apoptosis and inhibition of neurite outgrowth in SH-SY5Y cells. (June 2020) - Zhang, Ruisan; Luan, Jing; Hu, Fengrui; Lv, Jiaming; Zhang, Jieyuan; Li, Kang; Guo, Huifang; Cheng, Jianghong; Chen, Peng; Zhang, Yuelin; Cai, Qiang; Gou, Xingchun
Abstract: Alzheimer's disease (AD) is a serious neurodegenerative disease. Senile plaques (SPs) in the extracellular space and neurofibrillary tangles (NFTs) in the intracellular areas of the brain are two typical features of AD. SPs and NFTs are composed of amyloid-β (Aβ) aggregates and hyperphosphorylated Tau, respectively. (m)RVD-hemopressin (RVD), which is derived from mouse brain peptide, binds to the cannabinoid 1 receptor (CB1R) as an agonist. Our previous study indicated that RVD reversed Aβ1–42-induced memory impairment in mice. Here, we investigated the underlying molecular mechanism of RVD on Aβ1–42-induced neurotoxicity in retinoic acid-differentiated human neuroblastoma SH-SY5Y cells. Cell viability and neurite outgrowth were investigated by live cell imaging and analysis instrument. We found that RVD reversed Aβ1–42-induced Tau phosphorylation, apoptosis and suppression of neurite outgrowth and the synapse-associated protein postsynaptic density protein 95 (PSD-95) by inhibiting the activity of protein kinase A (PKA) and glycogen synthase kinase 3β (GSK-3β). Combined treatment with AM251 (a CB1R antagonist) blocked the effects of RVD. In conclusion, RVD may be a potential therapeutic agent for the treatment of cognitive dysfunctions, such as Alzheimer's disease.